2017
DOI: 10.3390/e19110584
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Reprogramming in Mouse Embryo Development through a Critical Transition State

Abstract: Our previous work on the temporal development of the genome-expression profile in single-cell early mouse embryo indicated that reprogramming occurs via a critical transition state, where the critical-regulation pattern of the zygote state disappears. In this report, we unveil the detailed mechanism of how the dynamic interaction of thermodynamic states (critical states) enables the genome system to pass through the critical transition state to achieve genome reprogramming right after the late 2-cell state. Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A mature mammalian somatic cell can reprogram its state (and consequently acquire a very different gene expression profile) through a few reprogramming stimuli [ In our previous studies [Tsuchiya, M., et al, 2014[Tsuchiya, M., et al, -2017Giuliani, A., et al, 2018], we have demonstrated the existence of self-organization in whole genome expression at both the population and single cell level that constitutes a 'physically motivated' alternative to the genespecific regulation. The mechanism of self-organization eliminates massive changes in the expression profile through the genome reprogramming inside a small and highly packed cell nucleus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mature mammalian somatic cell can reprogram its state (and consequently acquire a very different gene expression profile) through a few reprogramming stimuli [ In our previous studies [Tsuchiya, M., et al, 2014[Tsuchiya, M., et al, -2017Giuliani, A., et al, 2018], we have demonstrated the existence of self-organization in whole genome expression at both the population and single cell level that constitutes a 'physically motivated' alternative to the genespecific regulation. The mechanism of self-organization eliminates massive changes in the expression profile through the genome reprogramming inside a small and highly packed cell nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent behavior (i.e., CM dynamics) emerges in stochastic expression (coherent-stochastic behavior) in each critical state. These coherent behaviors exhibit a universal genome-engine mechanism [Tsuchiya, M., et al, 2016[Tsuchiya, M., et al, , 2017 for SOC-control of genome expression; the subcritical state (ensemble of low-expression variance genes) is a generator that sustains the SOC control forming a dominant expression cyclic flux between sub-and super-critical (highexpression variance genes) states through the cell nuclear environment. sorted and grouped according to fold-change in expression between two different time points (e.g., between t = 0 and t =10min).…”
Section: Introductionmentioning
confidence: 99%
“…A mammalian mature stem cell can reprogram its state to acquire a very different gene expression profile through a few reprogramming stimuli [ In our studies [Tsuchiya, M., et al, 2014[Tsuchiya, M., et al, -2017Giuliani, A., et al, 2018], we have demonstrated the existence of self-organization in whole genome expression at both population and single cell level. A fundamental issue is to elucidate the mechanism of the self-organization at the 'whole genome' level of gene-expression regulation that is responsible for massive changes in the expression profile through the genome reprogramming inside a small and highly packed cell nucleus.…”
Section: Introductionmentioning
confidence: 80%
“…suggests that reprogramming occurs after the memory of initial state of the CP (e.g., zygote state) is lost (i.e., after the temporal CM correlation of the CP group pass zero-correlation: Figure 4B); the timing of this correlation event coincided with the timing of erasure of initialstate criticality for mouse and human embryo developments [Tsuchiya, M., et al, 2017;Giuliani, A., et al, 2018]. Furthermore, the timing of global perturbation on single-cell genome expression coincides with that of reprogramming (Figure 6B), which suggests that the activation of the CP occur when the initial-state CP memory is erased.…”
Section: Regarding Reprogramming Of Human and Mouse Embryo Cells (Sinmentioning
confidence: 99%
See 1 more Smart Citation